Evaluation of implementation of accounting systems in an effort to minimize uncollective accounts - Justus Saferius Berek (Keynesia : International Journal of Economy and Business, 2022)
This research was conducted with the aim of knowing the Accounting System for Doubtful Accounts at KSU Tandangsari and the efforts made by KSU Tandangsari to utilize Accounting Information in minimizing Uncollectible Receivables. In this study, the authors use qualitative research. Data collection techniques used in this study were interviews and documentation. Interviews by holding direct questions and answers to the head of the accounts receivable section. Documentation by asking directly for the data used in this study. The results in this study are that KSU Tandangsari's operation regarding the accounting information system on the treatment of bad debts is to use direct write-off, which can be seen from the balance sheet that there is no position or reserve account for bad debts in terms of assets or assets, but the losses from these uncollectible accounts the cooperative is not immediately abolished but this cooperative hopes that members who borrow money to return it immediately, but it's just that in the report it is not written as a loss or uncollectible account . Based on the results of the analysis that has been carried out, it can be concluded by the author that in the application of the accounting information system in this cooperative, especially in the post uncollectible accounts, it is good to confirm before making a bill to the members, while the application of the accounting information system on uncollectible accounts turns out to be a cooperative. This has not taken any follow up on this problem, so this cooperative does not yet have a rule regarding bad debts, but the cooperative management just hopes that the bad debts can still be paid by members to the cooperative.